2014
DOI: 10.1007/s00339-014-8741-4
|View full text |Cite
|
Sign up to set email alerts
|

Single-shot front-side nanoscale femtosecond laser ablation of a thin silver film

Abstract: Nano-and microscale holes, as well as related sub-ablative nanospikes and sub-micron bumps, were produced in a 30-nm thick silver film on a silica substrate by single femtosecond laser pulses with variable pulse energies, focused by different strong focusing optics. Characteristic laser energy deposition dimensions exceed the expected focal spots by nearly 2 microns, indicating the considerable lateral thermal transport in the film, while the effective hole formation thresholds decrease versus increasing numer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
9
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 31 publications
1
9
0
Order By: Relevance
“…By comparing the Ag ablation threshold values determined in other studies, as seen in Table , and having in mind the maximum applied laser fluence investigated in our experiments, one can see that it was lower than any of the reported ablation threshold values, which supports the lack of a predominant periodic structure in the Ag‐100 sample and delamination of the thin film. The latter could be addressed to the stresses and shockwaves generated by femtosecond laser irradiation, which create disruptions in the interface of film and substrate, and can cause delamination of thin metal films as stated by Gallais et al This effect can already be caused by a single‐pulse irradiation at higher fluences and thus subsequent pulses do not contribute to the ablation or patterning of silver thin film, but rather of the substrate, which was observed at our experiments.…”
Section: Resultssupporting
confidence: 71%
“…By comparing the Ag ablation threshold values determined in other studies, as seen in Table , and having in mind the maximum applied laser fluence investigated in our experiments, one can see that it was lower than any of the reported ablation threshold values, which supports the lack of a predominant periodic structure in the Ag‐100 sample and delamination of the thin film. The latter could be addressed to the stresses and shockwaves generated by femtosecond laser irradiation, which create disruptions in the interface of film and substrate, and can cause delamination of thin metal films as stated by Gallais et al This effect can already be caused by a single‐pulse irradiation at higher fluences and thus subsequent pulses do not contribute to the ablation or patterning of silver thin film, but rather of the substrate, which was observed at our experiments.…”
Section: Resultssupporting
confidence: 71%
“…In our opinion, these facts indicate that, for the thicker film, subsurface boiling takes place, which is, among other physical and chemical factors, the main driving process not only for microbump and nanojet formation on surfaces of thin films [2,10,12], but also for surface spallation in bulk materials [13,14]. One possible reason for subsurface boiling can be the sub surface temperature maximum [5,[18][19][20][21][22][23], emerging on a sub nanosecond timescale within a thick film owing to a balance of heat conduction and intense evaporative cooling, as experimentally demonstrated in [15].…”
mentioning
confidence: 84%
“…A rather good approximation in understanding the mecha nisms of nanoscale ablation is the description of mac roscopic femtosecond (fs) laser ablation provided in a number of recent studies [9][10][11][12][13][14][15]. In particular, it was demonstrated that spallative femtosecond laser abla tion of thin films and bulk materials is initiated by delayed subsurface boiling of a molten layer [13,14], rather than thermoelastic stresses, with picosecond evaporative cooling of the layer suppressing its phase explosion [15].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…These can vary from random micro-and nanostructures, [20][21][22] subsurface voids and microcracks, [23][24][25] to laser-induced periodic surface structures or ''ripples'', 13,18,[26][27][28][29][30] which are to a certain extent controlled by the laser wavelength and polarization, to micro/nanobumps and frozen nanojets generated with single tightly-focused ultrashort pulses. [31][32][33][34][35][36][37][38][39][40][41][42][43] The latter surface structures can be replicated into ordered arrays by means of interference between multiple beams. 31,44 The surfaces with arrays of metallic and non-metallic microbumps have many potential technological applications due to their unique properties, such as superhydrophobicity, 45,46 self-cleaning, 47 and enhanced tribological performance, 48 as well as their active and nonlinear optical response.…”
Section: Introductionmentioning
confidence: 99%